Reactivation of a Vaccine Escape Hepatitis B Virus Mutant in a Cambodian Patient During Anti-Hepatitis C Virus Therapy - Fusco, Dahlene N.; Ganova-Raeva, Lilia; Khudyakov, Yury; Punkova, Lili; Mohamed, Aisha; Cheon, Scarlett Se Yun; Koirala, Prapti; Andersson, Karin L.; Jourdain, Gonzague; Sureau, Camille; Chung, Raymond T.; Lauer, Georg (Frontiers in Medicine, 2018)
A 76 year old Cambodian man co-infected with HBV and HCV 6c-1 presented for care. HBV DNA was intermittently detectable despite anti-HBs levels being above the protective threshold. During treatment for HCV, HBV DNA levels increased. Sequencing revealed multiple mutations including vaccine escape mutation and mutations predicted to enhance fitness. This case represents exacerbation of HBV-vaccine escape mutant during direct acting antiviral therapy.